Organ Donor Policy in Canada: Valuing Inclusion - Ashcroft, Rachelle (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2009)
Organ Donor Policy in Canada: Valuing InclusionOrgan, cell, and tissue transplantation has become a common worldwide procedureas knowledge, technology, and skills have developed in this area. Policies relatingto all aspects of organ, tissue, and cell donation have emerged in countries aroimdthe world in response. An issue that has generated debate is how to ensuresufficient supply of organs to meet the growing demand while ensuring that risksto patients are minimized and quality of care is maximized. In attempting to incorporatethese conditions into its proposed new standards, Canada has produced apolicy that contains exclusionary criteria directed at men who have sex with men(MSM). The position taken in this paper is that the criteria of minimizing risk and~naximizingq uality can be achieved without this exclusionary impact.Health Canada's standards in Safety of Human Cells, Tssues and Organs jorTransplantation (2009) are reviewed using a risk theory framework that comprisescomponents of the "risk society" with a "cultural/symbolic" theoretical lens. Therisk framework provides insight into reasoning behind the donor exclusionarycriteria in an attempt to maximize safety. This facilitates a critical investigationinto the underlying forces and meanings inherent within the document. Thisframework is also used to illustrate why the current Health Canada standardsare redundant and discriminatory. Subsequently, alternatives are proposed to theexisting cell, tissue, and organ do~~a t ioponl icy statements that address minim~zationof risk but reduce the exclusio~~ariryn pact on MSM by taking into accountexisting technology. This paper critically focuses on the policy position taken by Health Canada.The reason for this is twofold. Firstly, reflexivity related to Canadian transplantpolicy assists in filling a gap in the literature. Reflexivity encourages awareness tothe personal, social, cultural and political processes that influence and shape policy.In their overview of Ulrich Beck's conception of the risk society, Lash & Wynne(1992) describe, following Beck that "in order for societies really to evolve inodernizationmust become reflexive." Secondly, reflexivity is often "excluded from thesocial and political interactions between experts and social groups over modemrisks, because of the systematic assuil~ptiono f realism in science" (4).This paper strives to engage in and encourage reflexivity in the area ofCanadian transplant policy. As Cal~adiavia~l ues and legal principles deter discriminationbased on group membership; in this case MSM, alternative approaches tomaximizing safety in organ transplantation without the promotion of discrirninationneed to be considered.(Les politiques visant les dons d'organes au Canada : valoriser l'inclusion)Les crit2res d'exclusion qui ciblent les hornmes ayant des rapports sexuels avec des hornrnes21 l'e'gard des dons d'organes continuent h Etre renforcQ duns les politiques visant les donsd'organes et les transplantations au Canada. Ayant pour cadre la the'orie des risques, lespolitiques en vigueur au palier fe'de'ral pour les dons d'organes et les transplantations sontanalyse'es en visant particulierement la cornposante d'exclusion. Les politiques fe'dirales envigueur peuvent faire l'objet de re'visions qui minimisent les risques et garantissent laquulite' des soins, tout en pe'conisant l'inclusion sociale. Pour que les politiques canadiennesvisant les dons d'organes et les transplantations soient h la hauteur des connaissances etde la technologie actuelle, l'exclusion collective h l'e'gard des hornmes qui ont des rapportssexuels avec &S hommes pour ce qui est du don d'organes ne'cessite une re'vision